Breast milk: its components and special effects on newborns and infants - Voroncova, T.; Konyk, T.; Trokhymenko, M.; Mudryk, Y. (Journal of Education, Health and Sport, 2025)
Background. Breastfeeding is the gold standard of infant nutrition, ensuring optimal growth, development, and formation of the immune system during the first six months of life. Breast milk is a unique biological medium that contains both macro- and micronutrients, and bioactive components such as bacteria, immunoglobulins, lactoferrin, oligosaccharides, stem cells, and microRNAs. These compounds play a key role in the formation of the intestinal microbiota of newborns, affecting immunity, metabolism, neurodevelopment, and psychoemotional state. Changes in the microbiome due to the type of feeding are associated with long-term risks of allergies, obesity, type 2 diabetes, autoimmune and infectious diseases. Despite significant progress in the study of breastfeeding, the mechanisms of interaction between its bioactive components and the intestinal microbiota remain poorly understood, necessitating a systematic analysis of current data. The aim of the study was to evaluate the relationship and impact of breastfeeding on the formation of the gut microbiome, immune system and neurodevelopment of infants, with a detailed look at the bioactive components of breast milk, such as microbiota, oligosaccharides, complement, immunoglobulins, stem cells and microRNAs. Materials and methods. To achieve this goal, a systematic literature review was conducted using PubMed, Scopus and Google Scholar databases. The search was carried out using the following keywords: ‘human milk’, “milk microbiota”, “newborn's immune system”, “breastfeeding”. Preference was given to systematic reviews, clinical trials, and analytical articles published in English. The analysis covered current, verified data on the composition of breast milk and its impact on the microbiota and infant health. Results. A systematic review found that breast milk is a dynamic biological medium that adapts to the needs of the infant through gradual changes in composition from colostrum to mature milk. Colostrum, which is rich in immunoglobulins (including IgA), lactoferrin, leukocytes and epidermal growth factor, provides primary immune defence by stimulating tissue regeneration and intestinal barrier function. Transitional milk, which appears on days 4-14, increases the energy value due to increased lactose and fat content, promoting weight gain and microbiota development. Mature milk stabilises the nutritional profile, supporting growth and metabolism due to its high content of lipids, carbohydrates, and micronutrients such as vitamins A, B and D, depending on the mother's diet. The microbiota of milk, which includes hundreds of bacterial species (Streptococcus, Staphylococcus, Bifidobacterium, Lactobacillus), forms the intestinal microbiome, reducing the risk of dysbiosis and infections by competitively displacing pathogens and stimulating anti-inflammatory cytokines. Milk oligosaccharides act as prebiotics, promoting the growth of beneficial bacteria and preventing pathogen adhesion, which strengthens the intestinal barrier. Short-chain fatty acids (SCFAs), metabolites of bacteria, modulate the immune system, reducing the risk of atopic diseases, although their levels are reduced in mothers with allergies. Lactoferrin has antimicrobial, antifungal, and immunomodulatory effects, supporting the growth of beneficial microorganisms. Complement components selectively regulate the microbiota, destroying gram-positive bacteria, which contributes to microbial balance. Immune cells (neutrophils, macrophages, lymphocytes) and peptides (α-lactalbumin, casein, lysozyme) provide protection and digestion, while stem cells and microRNAs influence epigenetic regulation, promoting neurodevelopment and immune maturation. Conclusions. Breastfeeding, through the synergy of bioactive components, promotes a healthy intestinal microbiota, supports immunity and neurodevelopment, reducing the risk of allergies, metabolic and neurological disorders. However, the mechanisms of action of individual components, such as microRNAs, stem cells and the impact of maternal diet, require further research. The results highlight the importance of supporting breastfeeding for infants, as there is currently no infant formula that reproduces the bioactive properties of breast milk.